Succeeding as a frontline manager in today's organizations - Sims, Ronald R. (Emerald Publishing Limited : INFORMATION AGE PUBLISHING, INC., 2020)
"Succeeding as a Frontline Manager in Todays Organizations, highlights the fact that as the world of work continues to change in response to a variety of trends, issues and opportunities, manages on the frontline will still be expected to see that their organizations operate both effectively and efficiently to not only survive but to thrive. To do this, frontline managers (FLMs) must continue to learn and develop their skills to get the organization's work done through its people. This book examines both the traditional and contemporary skills todays frontline managers must have at a minimum and those they must successfully learn to implement to fulfill their critical roles and responsibilities. The book argues that FLMs will continue to play a critical role in helping their organizations pursue and achieve their strategic, tactical and operational goas efficiently and effectively. By focusing on the skills a good FLM needs, this book offers specificity on what the FLM and their organizations must do to increase the potential for the success of FLMs in having a positive influence on the organization overall by focusing both on results and the well-being of employees. The book examines not only looks at the essentials of effective management but discusses the importance of how one becomes and makes a smooth transition to the role of a FLM. In addition, the book examines the essential elements of management-planning, organizing, controlling, and leading-while also offering an in-depth look at the important role FLMs can and should play as it relates to ethics, building and leading effective teams, and safety and health. Each chapter offers insights into what FLMs can do to be effective in their work, particularly for those FLMs who want to continue to develop themselves as they play the different roles and exercise different skills in doing their jobs. In the end, this book is written for, those who are interested in increasing their understanding of the FLMs role, responsibilities and skills needed to be effective while also getting those who work for them to accomplish their work effectively, efficiently and productively on their own or as a member of a group or team"-- Provided by publisher.
Keywords: Personnel management.; Industrial management.; Teams in the workplace.; Leadership.; Business & Economics -- Industrial Management.; Personnel and human resources management.; Management and management techniques.; elektronické knihy; electronic books